2020
DOI: 10.7717/peerj.10413
|View full text |Cite
|
Sign up to set email alerts
|

Four sesquiterpene glycosides from loquat (Eriobotrya japonica) leaf ameliorates palmitic acid-induced insulin resistance and lipid accumulation in HepG2 Cells via AMPK signaling pathway

Abstract: Insulin resistance (IR), caused by impaired insulin signal and decreased insulin sensitivity, is generally responsible for the pathophysiology of type 2 diabetes mellitus (T2DM). Sesquiterpene glycosides (SGs), the exclusive natural products from loquat leaf, have been regarded as potential lead compounds owing to their high efficacy in hypoglycemia and hypolipidemia. Here, we evaluated the beneficial effects of four single SGs isolated from loquat leaf, including SG1, SG2, SG3 and one novel compound SG4 again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…For quantification, nerolidol-3- O - α - l -rhamnopyranosyl-(1→4)- α - l -rhamnopyranosyl-(1→2)-[ α - l -rhamnopyranosyl-(1→6)]- β -D-glucopyranoside (SG1), nerolidol-3- O - α - l -rhamnopyranosyl-(1→4)- α - l -rhamnopyranosyl-(1→2)- β -D-glucopyranoside (SG2), nerolidol-3- O - α - l -rhamnopyranosyl-(1→2)-[ α - l -rhamnopyranosyl-(1→6)]- β -D-glucopyranoside (SG3), and nerolidol-3-O- α - l -arabinopyranosyl-(1→4)- α - l -rhamnopyranosyl-(1→2)-[ α - l -rhamnopyranosyl-(1→6)]- β -D-glucopyranoside (SG4) were purified as standard compounds, and the same conditions were applied to HPLC. The chemical structure of SG1-4 is shown in Figures 1(b) and 1(c) and was consistent with the reported literatures [ 35 , 37 – 39 ].…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…For quantification, nerolidol-3- O - α - l -rhamnopyranosyl-(1→4)- α - l -rhamnopyranosyl-(1→2)-[ α - l -rhamnopyranosyl-(1→6)]- β -D-glucopyranoside (SG1), nerolidol-3- O - α - l -rhamnopyranosyl-(1→4)- α - l -rhamnopyranosyl-(1→2)- β -D-glucopyranoside (SG2), nerolidol-3- O - α - l -rhamnopyranosyl-(1→2)-[ α - l -rhamnopyranosyl-(1→6)]- β -D-glucopyranoside (SG3), and nerolidol-3-O- α - l -arabinopyranosyl-(1→4)- α - l -rhamnopyranosyl-(1→2)-[ α - l -rhamnopyranosyl-(1→6)]- β -D-glucopyranoside (SG4) were purified as standard compounds, and the same conditions were applied to HPLC. The chemical structure of SG1-4 is shown in Figures 1(b) and 1(c) and was consistent with the reported literatures [ 35 , 37 – 39 ].…”
Section: Methodssupporting
confidence: 91%
“…According to earlier studies, extracts of loquat leaves reduced TC and promoted glucose uptake in HFD-induced IR condition, which was instrumental in treating IR [ 43 , 44 ]. Our previous investigation indicated that sesquiterpene glycosides from loquat leaves exhibited the bioactivity of reducing lipid accumulation and enhancing glucose uptake in insulin-resistant HepG2 cells via AMPK pathway [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high insulin-induced insulin-resistant HepG2 cells model was established according the related references. [21][22][23] HepG2 cells were cultured in DMEM containing 10% FBS, 100 U/mL penicillin and 100 mg/mL streptomycin in 5% CO 2 in a humidified atmosphere. After the cells achieved about 80% confluence, the medium was changed and high concentration of insulin (30 μM) was supplemented to induce insulin-resistant model.…”
Section: Insulin Resistance Model Establishmentmentioning
confidence: 99%
“…More than fourth metabolites incldung ursolic acid, ursolic acid methyl ester, acetyl ursolic acid, and oleanolic acid, chlorogenic acid, neochlorogenic acid, caffeic acid with potential medicinal value have been detected in different organs of loquat by classical instrumental analyses [51,52] . However, Traditional phytochemistry methods are very time-consuming, and labor intensive and low-throughput.…”
Section: Discussionmentioning
confidence: 99%